2012
DOI: 10.7550/rmb.24868
|View full text |Cite
|
Sign up to set email alerts
|

Flora planctónica de laguna Lagartos, Quintana Roo Roo

Abstract: Las cianofitas dominaron durante todo el periodo de estudio, con una contribución mayor al 80% de la abundancia total del fitoplancton. Son nuevos registros para México l3 especies:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
0
2
0
6
Order By: Relevance
“…Novelo (2011) reported it for San Lorenzo spring (Tehuacán) and San Bernardino Lagunas and Laguna Mayor (Vicente Guerrero), Puebla. Finally, Nava-Ruiz and Valadez-Cruz (2012) and Valadez et al (2013) reported it for Lagartos Lagoon, Quintana Roo. For Limnoraphis birgei, the only record was by Gaytán-Herrera et al (2011) for the Valle de Bravo reservoir, Estado de Mexico; where L. birgei was one of the dominant species.…”
Section: Discussionmentioning
confidence: 91%
“…Novelo (2011) reported it for San Lorenzo spring (Tehuacán) and San Bernardino Lagunas and Laguna Mayor (Vicente Guerrero), Puebla. Finally, Nava-Ruiz and Valadez-Cruz (2012) and Valadez et al (2013) reported it for Lagartos Lagoon, Quintana Roo. For Limnoraphis birgei, the only record was by Gaytán-Herrera et al (2011) for the Valle de Bravo reservoir, Estado de Mexico; where L. birgei was one of the dominant species.…”
Section: Discussionmentioning
confidence: 91%
“…La identificación de las especies se realizó mediante guías y claves especializadas de algas dulceacuícolas (principalmente Komárek & Anagnostidis, 1999;Komárek & Anagnostidis, 2005;Komárek & Komárková-Legnerová, 2007;Nava-Ruiz & Valadez, 2012;Tavera et al, 2013;Wehr & Sheath, 2003). Una vez reconocidas, se recurrió a las bases de datos AlgaeBase (Guiry y Guiry, 2022) y bdLACET (Novelo & Tavera, 2022) para verificar el estado nomenclatural y su distribución, dando prioridad a la región de la Península de Yucatán.…”
Section: Trabajo De Laboratorio Y Gabineteunclassified
“…Distribución regional: Quintana Roo: Tulúm (López-Adrián & Barrientos-Medina, 2005;Nava-Ruiz & Valadez, 2012). Yucatán: Huhí (Díaz, 1999).…”
Section: Especieunclassified
See 1 more Smart Citation
“…They could be vulnerable to the action of climate-change variables, but to the best of our knowledge, no studies have addressed their potential impact (particularly of UVR and temperature) on natural phytoplankton communities. Indeed, most phytoplankton studies carried out in cenotes of the Yucatán Peninsula were descriptions of limnological characteristics or taxonomic studies (Cervantes-Martínez et al 2002, Sánchez et al 2002, Schmitter-Soto et al 2002, Nava-Ruiz and Valadez 2012, Tavera et al 2013, Valadez et al 2013. To fill this gap, we chose 2 cenotes that fell within the range of biological and physical characteristics (as reported in previous descriptive studies carried out in the Yucatán Peninsula) but differed in their light regime.…”
mentioning
confidence: 99%